Sistem Penjaminan Mutu Perguruan Tinggi (SPM-PT) Di Fakultas Tarbiyah Dan Keguruan UIN Sunan Kalijaga Yogyakarta - Mochamad Nurhuda (Faculty of Tarbiyah Institut Agama Islam Tribakti (IAIT) Kediri, 2018)
This paper seeks to illustrate the implementation of Quality Assurance System of Higher Education (SPM-PT) in the Faculty of Tarbiyah and Teacher Training UIN Sunan Kalijaga Yogyakarta, with the problem of why the quality targets in the Faculty of Tarbiyah and Teacher Training UIN Sunan Kalijaga have not been achieved and how the implementation of university quality assurance system at the Faculty of Tarbiyah and Teacher Training UIN Sunan Kalijaga. Quality assurance of higher education in universities is the process of implementing and fulfilling the standard of management and higher education consistently and continuously, so that stakeholders (students, parents, the world of work, government, lecturers, support staff, and other interested parties) get satisfaction. Tulisan ini berusaha menggambarkan implementasi Sistem Penjaminan Mutu Perguruan Tinggi (SPM-PT) di Fakultas Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, dengan rumusan masalah mengapa target mutu di Fakultas Tarbiyah dan Keguruan UIN Sunan Kalijaga belum tercapai dan bagaimana pelaksanaan sistem penjaminan mutu perguruan tinggi pada Fakultas Tarbiyah dan Keguruan UIN Sunan Kalijaga. Penjaminan mutu perguruan tinggi di perguruan tinggi adalah proses penerapan dan pemenuhan standar mutu pengelolaan dan pendidikan tinggi secara konsisten dan berkelanjutan, sehingga stakeholder (mahasiswa, orang tua, dunia kerja, pemerintah, dosen, tenaga penunjang, serta pihak lain yang berkepentingaan) memperoleh kepuasan.